2018
DOI: 10.3390/en11113015
|View full text |Cite
|
Sign up to set email alerts
|

Study on Vibration Transmission among Units in Underground Powerhouse of a Hydropower Station

Abstract: Research on the safety of powerhouse in a hydropower station is mostly concentrated on the vibration of machinery structure and concrete structure within a single unit. However, few studies have been focused on the vibration transmission among units. Due to the integrity of the powerhouse and the interaction, it is necessary to study the vibration transmission mechanism of powerhouse structure among units. In this paper, field structural vibration tests are conducted in an underground powerhouse of a hydropowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Castelli et al [202] studied the dynamic response of the Lentini earth dam in Sicily after the occurrence of the Santa Lucia earthquake and compared it with free-field 1D PLAXIS (plane strain and axial symmetry) simulation. Lian et al [203] studied the underground powerhouse of a hydropower station on the Yalong River in China using field structural vibration tests. They simplified the mechanical models and theoretically interpreted the transmission mechanism.…”
Section: Powerhouse Vibration Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…Castelli et al [202] studied the dynamic response of the Lentini earth dam in Sicily after the occurrence of the Santa Lucia earthquake and compared it with free-field 1D PLAXIS (plane strain and axial symmetry) simulation. Lian et al [203] studied the underground powerhouse of a hydropower station on the Yalong River in China using field structural vibration tests. They simplified the mechanical models and theoretically interpreted the transmission mechanism.…”
Section: Powerhouse Vibration Analysismentioning
confidence: 99%
“…The testing conditions for analysis were represented by another study using an FE model, and the results showed the propagation of the longitude-river vibration and vertical vibration was less than that of lateral-river vibration. The vibration transmission caused by the hydraulic generators' rotation was equivalent to that of the vibrations caused by the fluctuation of the low-frequency tail [203].…”
Section: Powerhouse Vibration Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…They found the vibration transmission direction in underground powerhouse was mainly perpendicular to and along the flow in the foundation rock. Lian et al (2018) concluded from the field structural vibration tests of an underground hydropower house that the transmission of lateral-river vibration was greater than those of longitude-river and vertical vibration and that the transmission ratios of vibration caused by the low and rotational frequency were basically equal. Sun and Yan (2013) proposed the time-delayed transfer entropy method to study the vibration of the hydropower house by numerical analysis of a simplified multistory structure and the prototype field experiment research.…”
Section: Introductionmentioning
confidence: 99%